Reception of Islamic Broadcasts of the Javanese Islamic Community in Wukirsari Village, Bantul Regency, Yogyakarta - Hidayat, Arief; Lasiyo Lasiyo; Sugeng Bayu Wahyono (CV. AFDIFAL MAJU BERKAH, 2025)
This article examines the reception of Islamic broadcasts within the Javanese Muslim community of Wukirsari Village, Bantul Regency, Yogyakarta. Drawing on Stuart Hall's encoding-decoding theory, the study seeks to understand how Islamic broadcasts are received and interpreted by individuals with a more flexible understanding of religion (abangan). The encoding process is carried out by media producers who convey Islamic messages through various programs, such as religious lectures and films. The decoding process within the Wukirsari community results in a range of interpretations of the encoded message, which align with the ideological positions of individuals, namely dominant-hegemonic, negotiated, or oppositional stances. This research employs a mixed-methods approach, combining the reception theory proposed by Stuart Hall (1980) and the phenomenological approach articulated by Chris Barker (2000), to explore how the Javanese Muslim community in Wukirsari Village interprets and interacts with religious television content. Through in-depth interviews and observations, the findings reveal that most individuals decode Islamic messages from a negotiated position, adapting the message to a more practical and contextually relevant understanding of religion.In conclusion, Islamic broadcasts play a crucial role in shaping the expression of collective religiosity. However, variations in the way the message is received and interpreted are evident, influenced by the social and cultural backgrounds of the audience